2019
DOI: 10.1123/jsr.2017-0182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hip Abduction Fatigue on Trunk and Shoulder Kinematics During Throwing and Passive Hip Rotational Range of Motion

Abstract: The hip abductor fatigue protocol utilized in this study did not significantly alter trunk and upper extremity throwing kinematics. The lack of changes may indicate that fatigue of the hip abductors does not contribute to trunk and shoulder kinematics during throwing or the protocol may not have been sport-specific enough to alter kinematics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Our single performance variable, exit velocity, was seldom a significant predictor of any knee kinetics. Due to the kinetic chain [44], we expected to find greater kinetics at the knee as exit velocity increased, under the assumption that increased force of the back leg would transmit into ball velocity. Also, to our surprise, height was a negative predictor of knee kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…Our single performance variable, exit velocity, was seldom a significant predictor of any knee kinetics. Due to the kinetic chain [44], we expected to find greater kinetics at the knee as exit velocity increased, under the assumption that increased force of the back leg would transmit into ball velocity. Also, to our surprise, height was a negative predictor of knee kinetics.…”
Section: Discussionmentioning
confidence: 99%
“…However, many factors can result in 'breaks' in the kinetic chain that disrupt efficient energy flow such as pain, insufficient muscular strength, or inadequate joint range of motion (ROM). [1][2][3][4] Among these factors, muscular strength and joint ROM are of particular interest to sports medicine professionals since they can be easily measured in a clinical setting.…”
Section: O N L I N E F I R S T Introductionmentioning
confidence: 99%
“…Adequate strength and mobility of the hip joint allows softball pitchers to achieve the most advantageous hip and pelvic position for postural control at foot contact. 5,6 Not only is this necessary for softball pitch execution and achieving high pitch speed, but research has also found that improper body positioning can increase injury susceptibility. 1,3 Research has linked decreases in passive hip ROM and strength with increased risk of injury in softball pitchers.…”
Section: O N L I N E F I R S T Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 6 , 18 , 19 , 44 , 45 Stability of the LPHC during dynamic upper-extremity movements is commonly associated with gluteal muscle activation resulting in pelvic stability. 5 , 20 , 21 , 25 , 30 , 35 , 37 39 It has been theorized that the LPHC provides the proximal stability for distal mobility, highlighting the role of the LPHC in providing a stable platform against which distal muscles can pull and accelerate. 18 Therefore, we define LPHC control as the ability to stabilize the LPHC in an effort to mobilize segments distal to the trunk.…”
mentioning
confidence: 99%